2013
DOI: 10.1111/hdi.12077
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Geriatric Nutritional Risk Index and total lymphocyte count and mortality of hemodialysis patients

Abstract: We examined the relationships between Geriatric Nutritional Risk Index (GNRI), total lymphocyte count (TLC), and mortality in hemodialysis (HD) patients. We examined GNRI and TLC in 120 maintenance HD patients and followed these patients for 120 months. Predictors of all-cause death were examined using life table analysis and the Cox proportional hazards model. TLC marginally correlated with GNRI (r = 0.176; p = 0.090) and significantly with phosphorus levels (r = 0.206; p = 0.026). Life table analysis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…There was no significant difference in patient characteristics or hematological variables including nutritional variables (total protein, serum albumin and lymphocyte count which sometimes used as a nutrition index [15,16]) between group C and group L. Pathological stage had not significant difference between two groups ( Table 2).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in patient characteristics or hematological variables including nutritional variables (total protein, serum albumin and lymphocyte count which sometimes used as a nutrition index [15,16]) between group C and group L. Pathological stage had not significant difference between two groups ( Table 2).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Shigenori Homma, Dr. Masahiro Takahashi, and Dr. Akinobu Taketomi have no conflicts of 16 interest or financial ties to disclose. b.…”
Section: Author Disclosuresmentioning
confidence: 99%
“…It is reported that the GNRI is a predictor of mortality in haemodialysis patients. 20 The mean GNRI values of the lowest and second lowest FGF-23 quartiles were <91.2, a level which is generally considered to be indicative of a requirement for nutritional support and to be a risk factor for sarcopenia and earlier mortality. 15 We consider that lower FGF-23 levels are significantly associated with malnutrition.…”
Section: Discussionmentioning
confidence: 93%
“…The patients in the lowest FGF‐23 quartile displayed the highest age, the shortest dialysis vintage, the lowest dosages of active vitamin D and phosphate binders, and the lowest BMI, nPNA, nPCR, GNRI, serum albumin, serum creatinine, serum phosphate, Ca, Ca × P product, and serum iPTH values among the FGF‐23 quartiles. It is reported that the GNRI is a predictor of mortality in haemodialysis patients . The mean GNRI values of the lowest and second lowest FGF‐23 quartiles were <91.2, a level which is generally considered to be indicative of a requirement for nutritional support and to be a risk factor for sarcopenia and earlier mortality .…”
Section: Discussionmentioning
confidence: 99%
“…15 In ad dition, TLC has been used as a measure of visceral This deserves further investigation in large-scale, prospective, long-term studies.…”
Section: The Equation For Opni Includes Serum Albuminmentioning
confidence: 99%